The Christian Witness of Monastic Life - Rossa, Piotr (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
Within the spectrum of Christian witness, monastic life has a pride of place. Presently it is understood in the Church as one of the forms of consecrated life. Its essence consists of putting on the «new man» after the example of Jesus Christ. This is accomplished through evangelical simplicity by practicing the evangelical counsels and living out the Beatitudes. The presence of Christians who exemplify this act of witness in their life in both eremitic and cenobitic forms has been a radical eschatological sign to the world throughout the centuries.